On Normothermic Regional Perfusion - Lee, Harrison (The Hastings Center report, 2024)
This letter responds to the article “Neither Ethical nor Prudent: Why Not to Choose Normothermic Regional Perfusion,” by Adam Omelianchuk et al., in the July-August 2024 issue of the Hastings Center Report.